2007
DOI: 10.1091/mbc.e07-05-0467
|View full text |Cite
|
Sign up to set email alerts
|

Src-mediated Phosphorylation of Hsp90 in Response to Vascular Endothelial Growth Factor (VEGF) Is Required for VEGF Receptor-2 Signaling to Endothelial NO Synthase

Abstract: Nitric oxide (NO) release from endothelial cells, via endothelial NO synthase (eNOS) activation, is central to the proangiogenic actions of vascular endothelial growth factor (VEGF). VEGF signaling to eNOS is principally mediated byan Akt-dependent phosphorylation of eNOS and by increased association of eNOS to the molecular chaperone, heatshock protein 90 kDa (Hsp90). Herein, we report that VEGFR-2 activation induces tyrosine phosphorylation of VEGF receptor 2 (VEGFR-2)-associated Hsp90␤. Tyrosine phosphoryla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
90
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(99 citation statements)
references
References 49 publications
8
90
1
Order By: Relevance
“…Moreover, we detected tyrosine phosphorylation of Hsp90, which recently has been connected to Hsp90 functions in vascular endothelial growth factor receptor-2 signalling (Duval et al, 2007). However, the functional consequence of Hsp90 tyrosine phosphorylation in our model system is not understood and warrants further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…Moreover, we detected tyrosine phosphorylation of Hsp90, which recently has been connected to Hsp90 functions in vascular endothelial growth factor receptor-2 signalling (Duval et al, 2007). However, the functional consequence of Hsp90 tyrosine phosphorylation in our model system is not understood and warrants further investigation.…”
Section: Discussionmentioning
confidence: 80%
“…Phosphorylation at S225 and S254 in Hsp90 causes a decreased affinity for the aryl hydrocarbon receptor (AhR) (Ogiso et al, 2004). In another example, c-src directly phosphorylates Hsp90 on Y300 and unlike other clients this phosphorylation event is required for the binding of eNOS to Hsp90 (Duval et al, 2007). Further studies will be required to determine the effect of phosphorylation on the conformation of Hsp90.…”
Section: The Effect Of Phosphorylation and Acetylation On The Conformmentioning
confidence: 99%
“…27 A recent study reported that c-Src directly phosphorylates Tyr300 of human Hsp90β. 32,33 This is essential for VEGF-stimulated endothelial nitric oxide synthase (eNOS) association with Hsp90 and thus is necessary for nitric oxide release from endothelial cells. 33 Another study reported that tyrosinephosphorylated Hsp90 repressed the function of ionotropic P2X 7 receptors.…”
Section: Tyrosine Phosphorylation Of Hsp90mentioning
confidence: 99%
“…32,33 This is essential for VEGF-stimulated endothelial nitric oxide synthase (eNOS) association with Hsp90 and thus is necessary for nitric oxide release from endothelial cells. 33 Another study reported that tyrosinephosphorylated Hsp90 repressed the function of ionotropic P2X 7 receptors. These receptors serve as ligand-gated ion channels and are responsible for ATPdependent lysis of macrophages.…”
Section: Tyrosine Phosphorylation Of Hsp90mentioning
confidence: 99%